The graphic design teacher profile of 2013 and 2023 - Hurtado Espinosa, Cynthia Lizette (2025)
This research has two objectives, the first is to identify the changes in 10 years of the ideal teacher for students of the degree in Graphic Communication Design of the University Center of Art, Architecture and Design of the University of Guadalajara, and the second is to see how the teaching profile is shaped in 2023 from the student, administrative and the same teacher's perspective. This research is qualitative, conducted with open questions to students in 2013 and 2023, whose answers have been categorized and represent a historical comparative analysis, also a survey was conducted in 2023 to professors to express their teaching profile and have been taken as a reference the teaching profile of the learning units of the degree updated in that same year. The different perspectives point out the importance of a profile with socio-affective characteristics, communication, professional training, disciplinary updating and professional experience. It was concluded that a balance between all should be considered in order to generate a teaching profile that is defined in the programs of the learning units.